School violence / minor decision - causes - and effects on the personality of the child in the primary stage (Journal of the College of Basic Education, 2022)
The primary stage is one of the important stages in its impact on the various aspects of growth in the student, such as growth, such as cognitive and emotional growth... This (primary) stage is still continuing in particular, in particular, in a continuous need of studies and research in the development and upgrading of educational and educational ratios.From this current logic of the current search in recognition:1- Forms of violence among students according to the perceptions of primary school teachers.2 - The factors causing violence and aggression on the personality of the child in the primary stage and according to the perceptions of their teachers.3- Detecting the effects resulting from school violence in the personality of the child in the childhood stage as perceived by the teachers of the primary stage.4- Develop a proposed vision for the mechanisms and overcoming the forms of violence and its causes to improve the handling and education within the family and the educational and educational performance inside the school and the classroom.In order to achieve the objectives of the research, the two researchers prepared a questionnaire consisting of several fields, starting with an open question at its beginning and end. As for the fields of the closed questionnaire, it included four fields with (50) paragraphs distributed among them.- The research community consisted of all primary school teachers in Wasit governorate, and its sample included (200) male and female teachers distributed over (26) primary schools, distributed between Al-Aziziyah and Al-Suwaira districts who were chosen randomly.The search results resulted in:1- Obtaining a range of forms of violence among primary school students according to the perceptions of their teachers.2- Detection of the set of factors causing violence and school aggression among primary school students according to the perceptions of their teachers, including (school - family, societal - and self-) factors.3- Reaching the outcomes of the effects of violence and aggression on the personality of the student in the primary stage according to the perceptions of their teachers, including:Getting used to hurting others - weakening relationships and social bonds between students - generating reactions to revenge and revenge.